ASSOCIATION BETWEEN ANXIETY AND MENSTRUAL CYCLE IRREGULARITY AMONG ADOLESCENT GIRLS IN PUBLIC SENIOR HIGH SCHOOL 15 SEMARANG: A CROSS-SECTIONAL STUDY - Lia Mulyanti; Lailatul Nisfiyah; Nuke Devi Indrawati; Maria Ulfa Kurnia Dewi (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Menstrual disorders are a major reproductive health issue frequently experienced by adolescents. These issues generally include menstrual cycle instability, changes in menstrual flow, including abnormal or prolonged bleeding, and pain or discomfort often associated with dysmenorrhea or premenstrual syndrome. Irregular menstrual cycles are an indication of menstrual problems. Menstrual problems can be triggered by various factors, including psychological factors (stress, life pressures, anxiety, and physical exhaustion), hormonal imbalances, nutritional conditions, and organic abnormalities (such as inflammation, tumors, and injuries). Lifestyle, learning patterns, and psychological factors are some of the factors that can influence anxiety. Purpose to determine the relationship between anxiety levels and the menstrual cycle among female students at Public Senior High School 15, Semarang.Methods: The research method used was an analytical cross-sectional study. A sample of 65 female students was obtained using proportional stratified random sampling. This study utilized an anxiety questionnaire based on the Zung Self-Rating Anxiety Scale (ZSAS) and a menstrual cycle questionnaire. Results: The results of the study showed that most female students aged 17 years were 32 female students (49.2%), and 42 female students experienced moderate levels of anxiety (64.6%), 29 female adolescents (44.6%) experienced irregular menstrual cycles, and 36 female adolescents (55.4%) had regular menstrual cycles. Conclusion: There is a significant relationship between anxiety levels and menstrual cycles in female adolescents at SMA Negeri 15 Semarang, with a correlation coefficient value of - 0.599 and a significance value <0.001.